Two Distinct Populations of α1α6-Containing GABAA-Receptors in Rat Cerebellum - Scholze, Petra; Pökl, Michael; Längle, Severin; Steudle, Friederike; Fabjan, Jure; Ernst, Margot (Frontiers in Synaptic Neuroscience, 2020)
GABAA receptors are pentameric GABA-gated chloride channels. The existence of 19 different subunits (six α, three β, three γ, δ, ε, θ, π, and three ρ) in mammalian systems gives rise to an enormous theoretical diversity of GABAA receptor subtypes with distinct subunit composition and unique pharmacological properties. These receptors are already now the drug targets of several clinically used compounds, such as benzodiazepines, anesthetics, and many more. There is a constant quest to identify novel molecules and possible future drug targets: Currently, α6-containing GABAA receptors are being discussed in the context of treating sensorimotor gating deficits in neuropsychiatric disorders, such as tic disorders and schizophrenia. Therefore, we aim to learn more about α6-containing GABAA receptors. They are mostly expressed in the cerebellar granule cell layer, where they form the following subtypes: α6βxγ2, α1α6βxγ2, α6βxδ, and α1α6βxδ. In former studies, α1α6βxγ2-containing GABAA receptors were considered a single receptor population. In the current study, we investigate the possibility, that this population can consist of two subgroups with alternative arrangements depending if α1 neighbors γ2 (forming a “diazepam-sensitive” receptor), or if α6 neighbors γ2 (forming a “diazepam-insensitive” receptor) and aimed to prove the existence of both subtypes in native tissue. We performed immunoprecipitation experiments on rat cerebellar lysates using α1- or α6 subunit-specific antibodies followed by radioligand binding assays with either 3H-flunitrazepam or 3H-Ro 15-4513. Indeed, we were able to prove the existence of two distinct populations of α1α6-containing GABAA-receptors and could quantify the different receptor populations: α1βxγ2 receptors constitute approximately 60% of all γ2-containing receptors in the rat cerebellum, α6βxγ2 about 20%, and both isoforms of α1α6βxγ2 9–15% each. The simple classification of GABAA-receptors into αx-containing subtypes seems not to reflect the complexity of nature; those receptors are more diverse than previously thought.